Influence of powder properties on densification mechanism during spark plasma sintering. (October 2017) - Yang, C.; Zhu, M.D.; Luo, X.; Liu, L.H.; Zhang, W.W.; Long, Y.; Xiao, Z.Y.; Fu, Z.Q.; Zhang, L.C.; Lavernia, E.J.
Abstract: We report on the formulation of a factor, f, that when applied together with the activation energy for viscous flow ( Q ), can be used to provide important insight into the densification mechanism that are active during powder sintering. We ascertain the validity of this formulation by comparing the densification behaviour of atomized and milled powders for Ti-6Al-4V alloy and pure Ti during spark plasma sintering, and identifying the underlying mechanisms. Graphical abstract: We described a formulation that can be used to provide insight into the densification mechanism that are active in atomized and milled powders, during spark plasma sintering. The values of f (defined in terms of powder physical properties) and Q (activation energy for viscous flow) can be used to assess the mechanism that controls each stage of densifications.